2011
DOI: 10.1039/c1cc15638a
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the duocarmycin pharmacophore enables CYP1A1 targeting for biological activity

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 29 publications
4
47
0
Order By: Relevance
“…Together these data indicate that clinical bladder cancer could be specifically chemosensitized to ICT2700, a synthetic derivative of the ultrapotent duocarmycins that we have shown to be metabolically activated by CYP1A1 (19).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Together these data indicate that clinical bladder cancer could be specifically chemosensitized to ICT2700, a synthetic derivative of the ultrapotent duocarmycins that we have shown to be metabolically activated by CYP1A1 (19).…”
Section: Resultsmentioning
confidence: 96%
“…Efficacy against CYP1A1-expressing tumors, but not CYP1A1-null tumors provides compelling evidence for the importance of CYP1A1 in formation of a cytotoxic metabolite in vivo. The antitumor efficacy of the authentic metabolite ICT2740 has been shown previously to involve DNAalkylation (19). Importantly, although both ICT2700 and its authentic metabolite ICT2740 have shown potent antitumor activity in vivo, only ICT2740 administration was associated with body weight loss, an indicator of normal tissue toxicity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Certain isoforms, notably CYP1A1, 1B1 and 3A4 are identified as highly expressed in certain tumours 10 indicating the value of truncated azinomycin analogues as potential bioprecursors with chemotherapeutic efficacy. We have demonstrated proof of principle with bioprecursors of the duocarmycin natural products targeting CYP1A1 19,20 and 2W1 14,21 enzymes. Uniquely, we have demonstrated that CYP selective bioactivation in vivo can be obtained with no overt toxicity to normal tissues including the liver.…”
Section: Discussionmentioning
confidence: 99%